2001
DOI: 10.1557/proc-666-f3.10
|View full text |Cite
|
Sign up to set email alerts
|

Mobility in SnO2:F Thin Polycrystalline Films: Grain Boundary Effect and Scattering in the Grain Bulk

Abstract: Basic electronic properties relevant to the carrier mobility were studied in tin oxide thin films doped with fluorine, prepared by atmospheric pressure chemical vapor deposition. Electrical resistivity, Hall and Seebeck effects, plasma and collision frequencies were measured (the last two by using multiangle spectral ellipsometry) and analyzed for films with carrier concentrations from 1.8×1020 to 5.6×1020 cm−3. Scanning over the sample area of resistivity (four-point probe method) and Seebeck coefficient (the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 3 publications
1
7
0
Order By: Relevance
“…Therefore, it can be concluded that GBS is not a dominant process, even in high-quality epitaxial CdO films with modest carrier concentrations and small grain sizes, 2 × 10 20 cm -3 and ∼100 nm, respectively. This conclusion is in agreement with recent results suggesting that GBS should be insignificant in TCO films based on alternative, carrier mean-free-path arguments. ,,,, According to Zhang and Ma, a TCO with a useful conductivity will be degenerate with a high carrier concentration, limiting the carrier mean-free-path to a value much smaller than the grain size of typical films. The formulation for carrier mean-free-path is given in eq 8. , …”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Therefore, it can be concluded that GBS is not a dominant process, even in high-quality epitaxial CdO films with modest carrier concentrations and small grain sizes, 2 × 10 20 cm -3 and ∼100 nm, respectively. This conclusion is in agreement with recent results suggesting that GBS should be insignificant in TCO films based on alternative, carrier mean-free-path arguments. ,,,, According to Zhang and Ma, a TCO with a useful conductivity will be degenerate with a high carrier concentration, limiting the carrier mean-free-path to a value much smaller than the grain size of typical films. The formulation for carrier mean-free-path is given in eq 8. , …”
Section: Discussionsupporting
confidence: 91%
“…This conclusion is in agreement with recent results suggesting that GBS should be insignificant in TCO films based on alternative, carrier mean-free-path arguments. 17,18,21,23,24 According to Zhang and Ma, 18 a TCO with a useful conductivity will be degenerate with a high carrier concentration, limiting the carrier mean-free-path to a value much smaller than the grain size of typical films. The formulation for carrier mean-freepath is given in eq 8.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to Y- and Sc-doped CdO, , the mobilities and conductivities of CGO films are essentially independent of temperature in the low-temperature region (<100 K), suggesting that neutral impurity scattering (NIS) and/or ionized impurity scattering (IIS) processes are dominant. , In the high-temperature region (>100 K), the mobility and conductivity decrease with increasing temperature, suggesting that lattice vibration scattering (LVS), which is temperature-dependent, has now become an important scattering contributor. The importance of grain boundary scattering (GBS) is an incompletely resolved mechanistic issue in most CdO-based TCOs. It has been argued that GBS is insignificant for highly degenerate TCOs because the carrier mean free paths (determined optically) are typically much smaller than the grain sizes of typical films. ,, …”
Section: Resultsmentioning
confidence: 99%